Residents as Teachers: A Unique Approach to Teaching Infant Feeding and Normal Growth to Pediatric Residents in the Continuity Clinic Setting - Shareen Kelly; Regina Vince (Association of American Medical Colleges, 2015)
Abstract Residents in pediatric training programs are required to spend an average of one half-day per week in the outpatient setting learning to provide longitudinal well-child care and follow-up to a panel of patients for whom they are the primary care provider. In addition to this required clinical exposure with patients, our program includes a weekly didactic experience for the residents in this setting. We have chosen to develop our own curricula for use in the outpatient department and we emphasize the role of resident as teacher because we believe that in teaching others, personal learning is enhanced. This module includes a curriculum to teach the topics of infant feeding and growth in resident continuity clinic. We use our resident-as-teacher model to deliver curriculum content in outpatient general pediatrics, in this case surrounding evidence based practices dealing with the issues of infant feeding and normal infant growth. The residents enter both the teacher and learner roles as they prepare and deliver curricular content to their peers in our continuity clinic didactic lecture series. Residents use interactive teaching to engage varying learning styles and study guides and posttest material to assess effectiveness of learning.